Construct validity and reliability of an instrument to evaluate attention to student diversity in dance - Avila García, Yeny (2020)
The objective of this work was to perform the construct validity and reliability study of the CEADED instrument that evaluates attention to diversity among dance students at the university level. An instrumental study was carried out based on the following steps: 1) determine the validity of the construct through the use of factor analysis; and 2) analyze the reliability of the instrument. The instrument was applied to a sample of 453 dance professional students from various universities in Mexico, and the factorial analysis was carried out using the method of extraction of factorization of principal axes iterated with Oblimin Direct rotation. The factorial analysis showed eight factors that explained 65.260% of the variance and the reliability was of a Cronbach's alpha of 0.957.